2011
DOI: 10.1124/mol.111.071688
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Modal Activation of GluA3 Receptors

Abstract: AMPA receptors are the major excitatory neurotransmitter receptors in the central nervous system and are involved in numerous neurological disorders. An agonist-binding site is present in each of four subunits that form a functional channel. Binding consists of three steps: docking of agonist to the bilobed ligand binding domain (LBD), closure of the LBD, and increased stability of the closed-lobe conformation through interlobe hydrogen bonding. We describe GluA3 single channel currents activated by nitrowilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 45 publications
4
64
0
Order By: Relevance
“…1. The data shown in the bar graph are consistent with the numerous previous more detailed investigations and show that the willardiines are partial agonists with iodowillardiine have a lower response relative to chloro-and nitro-willardiines (31,32,39). A two-tailed repeated measures t test was performed for statistical analysis of differences in the measured currents, and a p value of Յ0.05 was considered significant in our experiments.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…1. The data shown in the bar graph are consistent with the numerous previous more detailed investigations and show that the willardiines are partial agonists with iodowillardiine have a lower response relative to chloro-and nitro-willardiines (31,32,39). A two-tailed repeated measures t test was performed for statistical analysis of differences in the measured currents, and a p value of Յ0.05 was considered significant in our experiments.…”
Section: Resultssupporting
confidence: 73%
“…Nitrowillardiine and cholorwillardiine have similar electrophysiological responses; however, the average smFRET distances indicate that the nitrowillardiine-bound state is on average slightly more closed relative to chlorowillardiine bound state. A similar breakdown was observed in the crystal structures where no significant changes were observed in the distances at the positions labeled for the FRET measurements between these willardiines (shown in Table 1) (39).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Single channel recording experiments (12) have demonstrated that full and partial agonists can activate AMPA receptor channels to the same three or four distinct conductance levels. At saturating agonist concentrations in the absence of desensitization, partial agonists exhibit lower currents than full agonists because the lower conductance levels are preferentially populated relative to that seen with full agonists (12,14,42). The different conductance levels have been assumed to arise from the activation of individual gates on each of four subunits (43).…”
Section: Discussionmentioning
confidence: 99%